Sex-Related Differential Prevalence of Central Obesity in Diabetes Mellitus: A Multi-centred Survey in North-Central Nigeria - Mshelia-Reng R; Lawal Y; Odiase SO; Shuaibu R; Odumodu K; Anumah FE (Annals of Health Research, 2023)
Background: Contrary to the old dictum that central obesity is more common among men than women, recent reports have shown a gradual reversal of this trend, as suggested by some studies.